H and D ∕ H analysis in olivine and wadsleyite with a multi-analytical approach combining Raman spectroscopy and ion and nuclear probes - A. Gautier; N. Bolfan-Casanova; B. Moine; H. Bureau; H. Khodja; A. C. Withers; L. Piani (European Journal of Mineralogy)
The most abundant mineral in the upper mantle, olivine, is described as nominally anhydrous, while its high-pressure polymorph, wadsleyite, can contain up to 3 % H2O by weight. Here we focus on the quantification of total H2O content, dissolved as hydroxyl (OH), as well as hydrogen isotopic composition, i.e. D/H<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="24pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="930dd7e3de32880de8db3a2da0740eed"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-37-305-2025-ie00004.svg" width="24pt" height="14pt" src="ejm-37-305-2025-ie00004.png"/></svg:svg> ratios, in olivine and wadsleyite using a multi-instrument approach. Our aim is to establish a calibration procedure that allows accurate quantification of the hydrogen content and D/H<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="24pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="e4022fe1fd207c62e15fbadd87aa382d"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-37-305-2025-ie00005.svg" width="24pt" height="14pt" src="ejm-37-305-2025-ie00005.png"/></svg:svg> ratios of D-doped experimental samples using Raman spectroscopy, as confirmed by secondary-ion mass spectrometry (SIMS). Olivine and wadsleyite samples were synthesized under hydrothermal conditions at high pressure and doped with deuterium. Olivine and wadsleyite reference materials that were previously characterized by both Fourier-transform infrared (FTIR) spectroscopy and elastic recoil detection analysis (ERDA) were used to calibrate the measurement of water concentrations in the samples using both Raman spectroscopy and SIMS. D-doped olivine reference materials were characterized by ERDA (which is a point beam technique with the advantage of being an absolute quantification method) to find their D/H<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="24pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="1a8248039cc78c598c0e30bf487dec86"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-37-305-2025-ie00006.svg" width="24pt" height="14pt" src="ejm-37-305-2025-ie00006.png"/></svg:svg> ratio and used to determine the instrument mass fractionation of H isotopes with the ion probe. Then we compared the D/H<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="24pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="c78995d3f67856633c35697a267d9112"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-37-305-2025-ie00007.svg" width="24pt" height="14pt" src="ejm-37-305-2025-ie00007.png"/></svg:svg> ratios determined by SIMS to the OD/OH<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="41pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="2cc1e29e7cbb5e6250616346ce803788"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-37-305-2025-ie00008.svg" width="41pt" height="14pt" src="ejm-37-305-2025-ie00008.png"/></svg:svg> intensity ratio determined by Raman spectroscopy for three wadsleyite samples, finding a conversion factor of 0.85 (error of ∼2 %). After correction of the instrument response, we find that the Raman scattering cross-section (K) of OH is slightly lower than that of OD; still KOH/KOD=0.95<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="81pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="c3bf3845ff844d5d2ce2456a7fe38c05"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-37-305-2025-ie00009.svg" width="81pt" height="14pt" src="ejm-37-305-2025-ie00009.png"/></svg:svg> is in agreement with previous studies. D/H<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="24pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="1da8140e20db6bd42f7b603d40e61948"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="ejm-37-305-2025-ie00010.svg" width="24pt" height="14pt" src="ejm-37-305-2025-ie00010.png"/></svg:svg> ratios in doped samples can therefore be determined using Raman spectroscopy, which is a more accessible technique than SIMS, with a detection limit of 90±10 ppm wt for both D2O and H2O.